Accuracy in Cement Hydration Investigations: Combined X-ray Microtomography and Powder Diffraction Analyses - Salcedo, Inés R.; Cuesta-García, Ana María; Shirani, Shiva; León-Reina, Laura; García-Aranda, Miguel Ángel (MDPI, 2021)
Cement hydration is a very complex set of processes. The evolution of the crystalline phases during hydration can be accurately followed by X-ray powder diffraction data evaluated by the Rietveld method. However, accurate measurements of some microstructural features, including porosity and amorphous content developments, are more challenging. Here, we combine laboratory X-ray powder diffraction and computed microtomography ( CT) to better understand the results of the CT analyses. Two pastes with different water–cement ratios, 0.45 and 0.65, filled within capillaries of two sizes, = 0.5 and 1.0 mm, were analysed at 50 days of hydration. It was shown that within the spatial resolution of the measured CTs, ~2 m, the water capillary porosity was segmented within the hydrated component fraction. The unhydrated part could be accurately quantified within 2 vol% error. This work is a first step to accurately determining selected hydration features like the hydration degree of amorphous phases of supplementary cementitious materials within cement blends.
Keywords: Microestructura; Porosidad; Portland cements; Rietveld method; 3D image segmentation; Microstructure; Porosity